2014
DOI: 10.3390/molecules190812349
|View full text |Cite
|
Sign up to set email alerts
|

Berberine, an Epiphany Against Cancer

Abstract: Alkaloids are used in traditional medicine for the treatment of many diseases. These compounds are synthesized in plants as secondary metabolites and have multiple effects on cellular metabolism. Among plant derivatives with biological properties, the isoquinoline quaternary alkaloid berberine possesses a broad range of therapeutic uses against several diseases. In recent years, berberine has been reported to inhibit cell proliferation and to be cytotoxic towards cancer cells. Based on this evidence, many deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(108 citation statements)
references
References 114 publications
(144 reference statements)
2
106
0
Order By: Relevance
“…Several studies on different cancer cells treated with BBR reported its ability to regulate (up/down) different proteins that trigger apoptosis or autophagy [5]. We previously found that some BBR derivatives (NAX012, NAX014, and NAX018, characterized by arylalkyl groups bonded to the C-13 position) are able to induce DNA damage and cell cycle arrest, inhibit cellular proliferation, and promote cell death through apoptosis in a p53-dependent manner [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on different cancer cells treated with BBR reported its ability to regulate (up/down) different proteins that trigger apoptosis or autophagy [5]. We previously found that some BBR derivatives (NAX012, NAX014, and NAX018, characterized by arylalkyl groups bonded to the C-13 position) are able to induce DNA damage and cell cycle arrest, inhibit cellular proliferation, and promote cell death through apoptosis in a p53-dependent manner [2].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the structure of BBR makes it an attractive natural lead compound for the introduction of various chemical modifications in appropriate positions of the skeleton [4]. In particular, arylalkyl derivatives of BBR characterized by aromatic groups bonded to the C-13 position of the parent BBR via a linker of variable length have been reported to have anticancer properties [1,2,5,6]. Recently, we analyzed a first set of BBR derivatives with a 13-(di) arylalkyl modification, which were demonstrated to exert anticancer effects on human p53 wt colon cancer cell lines [2].…”
Section: Introductionmentioning
confidence: 99%
“…Berberine was found to inhibit tumor cell proliferation and exhibited cytotoxicity towards tumor cells [96-104]. Berberine was shown inducing autophagic and apoptotic cell death in hepatocellular carcinoma HepG2, MHCC97-1, and SMMC7721 cells, as indicated in [101].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…[13] For instance, the natural product berberine shows therapeutic potential in treatment of cancer and diabetes, [14] and aspergillitine, isolated from Aspergillus versicolor in marine sponge, exhibited antibacterial activity against Bacillus subtilis . [15] Fluorine incorporation into isoquinoline has been proven to reduce in vivo metabolism, [16] particularly as a bioisostere of hydrogen to block oxidation at C-4 (the major metabolism), and thus serves as a valuable fluorine-containing component in pharmaceutical design, [17] for example Glanatec ® .…”
mentioning
confidence: 99%